Uncovering the Hidden Curriculum: Cultural Messages in Senior High School English Textbooks - Mukhtarul Anam; Riryn Fatmawaty; Setyo Nurvita Agustina; Fita Faridah (Universitas PGRI Madiun, 2026)
This study aims to identify the types of cultural values found in English learning materials for 11th-grade high school students and to analyze how these values are represented from the perspectives of students and teachers. Using a qualitative approach and Émile Durkheim’s theory of social facts, the study categorizes cultural values into four dimensions: externality, coerciveness, generality, and independence. The findings reveal that these values are embedded in narrative texts such as folktales and moral stories, serving both as language learning tools and character-building media. Externality and coerciveness are reflected in obedience to authority and social norms, while generality and independence appear in collective values and critical thinking. Students' reading skills also play a significant role in understanding and internalizing these values. Integrating cultural values into English instruction supports the development of literacy, character, and students’ cultural awareness.